Pulmonary Thromboembolism following Russell’s Viper Bites - Subramanian Senthilkumaran; Sasikumar Sampath; José R. Almeida; Jarred Williams; Harry F. Williams; Ketan Patel; Ponniah Thirumalaikolundusubramanian; Sakthivel Vaiyapuri (Toxins, 2024)
Snakebite envenoming and its resulting complications are serious threats to the health of vulnerable people living in rural areas of developing countries. The knowledge of the heterogeneity of symptoms associated with snakebite envenoming and their management strategies is vital to treat such life-threatening complications to save lives. Russell’s viper envenomation induces a diverse range of clinical manifestations from commonly recognised haemotoxic and local effects to several rare conditions that are often not reported. The lack of awareness about these unusual manifestations can affect prompt diagnosis, appropriate therapeutic approaches, and positive outcomes for patients. Here, we report pulmonary thromboembolism that developed in three patients following Russell’s viper envenomation and demonstrate their common clinical features and diagnostic and therapeutic approaches used. All patients showed clinical signs of local (oedema) and systemic (blood coagulation disturbances) envenomation, which were treated using polyvalent antivenom. They exhibited elevated heart rates, breathlessness, and reduced oxygen saturation, which are non-specific but core parameters in the diagnosis of pulmonary embolism. The recognition of pulmonary embolism was also achieved by an electrocardiogram, which showed sinus tachycardia and computed tomography and echocardiogram scans further confirmed this condition. Anti-coagulant treatment using low-molecular-weight heparin offered clinical benefits in these patients. In summary, this report reinforces the broad spectrum of previously unreported consequences of Russell’s viper envenomation. The constant updating of healthcare professionals and the dissemination of major lessons learned in the clinical management of snakebite envenoming through scientific documentation and educational programs are necessary to mitigate the adverse impacts of venomous snakebites in vulnerable communities.